Frequency selective surface with switchable polarization. Issue 2 (February 2014) - Du, Guohong; Yu, Chengyang; Liu, Changjun
ABSTRACT This article presents a novel frequency selective surface (FSS) with switchable polarization, which is realized using the improved cross slots with embedded strips and isolated island structure. The transmission characteristics of FSS unit cell for both horizontal polarization and vertical polarization are simulated with CST. And a FSS made of an array of 20 × 20 cells is implemented on the substrate Rogers RO4003. The experiment results show that the proposed FSS can obtain polarization switching through short and open circuits for X‐band application. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:515–518, 2014